2005
DOI: 10.1002/anie.200500592
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ions as Cofactors for the Binding of Inhibitors to Methionine Aminopeptidase: A Critical View of the Relevance of In Vitro Metalloenzyme Assays

Abstract: Thiabendazole is a potent inhibitor of E. coli methionine aminopeptidase (MetAP) in vitro. Crystallographic structures of MetAP complexed with this and two other inhibitors show that binding is mediated by an auxiliary metal ion (see picture). This effect results from the high concentration of metal ions under in vitro conditions, and should be taken into account in assays for inhibitors of metal‐dependent enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 20 publications
4
55
0
Order By: Relevance
“…Metal ions such as Mg, Mn, Zn, Cu, Ca, Na and Fe are essential for cell mass formation and also they act as cofactors for several bio-synthetic enzymes (Schiffmann et al, 2005). In the present study it was found that 0.1 % of manganese enhanced the L-asparaginase production followed by copper sulphate and zinc sulphate (4.11 IU) and least activity by magnesium sulphate (3.83 IU) ( Figure-13).…”
Section: Metal Ionssupporting
confidence: 49%
“…Metal ions such as Mg, Mn, Zn, Cu, Ca, Na and Fe are essential for cell mass formation and also they act as cofactors for several bio-synthetic enzymes (Schiffmann et al, 2005). In the present study it was found that 0.1 % of manganese enhanced the L-asparaginase production followed by copper sulphate and zinc sulphate (4.11 IU) and least activity by magnesium sulphate (3.83 IU) ( Figure-13).…”
Section: Metal Ionssupporting
confidence: 49%
“…Purified MetAP apoenzyme can be reproducibly activated by a number of divalent metal ions, such as Co(II), Mn(II), Ni(II), and Fe(II) (11,12). Among them, Co(II) is one of the best activators of the enzyme, and many MetAP inhibitors were discovered by screening on purified MetAP with high Co(II) concentrations in the activity assay (13). Several x-ray structures of MetAP with or without an inhibitor bound showed that the catalytic site is a shallow pocket with two Co(II) ions situated at the bottom for a dinuclear arrangement (14).…”
mentioning
confidence: 99%
“…Potent MetAP inhibitors have been identified, but none of the inhibitors have shown significant antibacterial activity (13,22,23). Although most of the current MetAP inhibitors inhibit the Co(II)-form of MetAP effectively, their potency on other metalloforms often has not been characterized.…”
mentioning
confidence: 99%
“…Therefore, human MetAPs may also serve as targets for the development of new anticancer agents. Some small molecules that inhibit MetAPs potently in vitro are known, but they lack potent antibacterial (10)(11)(12) or antiangiogenic (13) activities. One reason for this failure may be that they do not penetrate the bacterial or mammalian cells to reach their intended target, or perhaps they are efficiently transported back out of the cells.…”
mentioning
confidence: 99%
“…These metal ions are suggested to bind and activate the water for deprotonation and assist the nucleophilic attack, whereas the metal ion M2 also binds the free unprotonated amino group of the methionine residue (P1) of the substrate for a productive bound conformation. In some recent structures, a third divalent metal ion is also present, serving as a bridge between a small molecule ligand and active-site groups on the enzyme (11,(22)(23)(24). Despite the great number of x-ray structures of these enzymes that show two or even three divalent metal ions bound in the active-site region, metal titration studies indicate that some of these metalloaminopeptidases can function fully with only a single metal ion bound.…”
mentioning
confidence: 99%